'Please tell me all you remember': a comparison between British and Arab interviewees' free narrative performance and its implications for lie detection. Issue 4 (4th July 2021) - Vrij, Aldert; Leal, Sharon; Mann, Samantha; Vernham, Zarah; Dalton, Gary; Serok-Jeppa, Or; Rozmann, Nir; Nahari, Galit; Fisher, Ronald P.
Abstract : We examined how much information British and Arab truth tellers and lie tellers volunteer in an initial free narrative. Based on cultural differences in communication styles we predicted that British interviewees would report more details and more complications than Arab interviewees (culture main effect). We further predicted that truth tellers would report more details and complications than lie tellers (veracity main effect), particularly in the British sample (Veracity × Culture interaction effect). A total of 78 British and 76 Israeli-Arab participants took part. The experiment was carried out at a British university and an Israeli university. Participants carried out a mission. Truth tellers were instructed to report the mission truthfully in a subsequent interview whereas lie tellers were asked to lie about certain aspects of the mission. The three hypotheses were supported for details, whereas for complications only the predicted veracity main effect occurred.